What Factors Drive the Dividend Policy of Indian Companies? - Wadhwa, Ritu (Indian Journal of Research in Capital Markets, 2019)
Dividend policy of companies is one of the most provocative issues of theoretical finance. The aim of this paper was to scrutinize the firm-level dynamics persuading the dividend decisions of companies in a developing economy. Twelve-year panel data from 2006-2018 of BSE-500 index were used for this study. Results revealed that most of the variables lying in the categories of profitability, risk, size, ownership, and financial leverage were found to be significant determinants of dividend policies of firms. However, sales growth and liquidity were not found to have a significant effect on dividend decision of the companies. The decision regarding the dividend policy is very crucial for the firms as it outlines the method, type, and frequency of dividend distribution. This present study adds to the prevailing literature by assessing the impact of 21 variables together on dividend policy of the firms. It provides a comprehensive framework that can be useful to companies, investors, and regulators of companies in India.